Stigma in the bereavement experiences of gay men who have lost a partner to suicide. Issue 11 (2nd November 2019) - Ferlatte, Olivier; Oliffe, John L.; Salway, Travis; Knight, Rod
Abstract: Despite the high prevalence of suicide in gay communities, the impact of suicide on surviving male partners is poorly understood. This article presents a qualitative case study of two gay men who lost a partner to suicide and explores how stigma may shape gay men's bereavement experiences. Data were collected using photovoice methods and analysed using a thematic approach. Five themes were inductively derived: (1) trying to prevent the inevitable; (2) guilty of keeping secrets; (3) dreams shattered by suicide; (4) abandoned and alone in grief; and (5) a lonesome road to recovery. Within each theme, the article indentifies how stigma-related challenges associated with suicide, mental illness and minority sexual identity shaped gay men's bereavement experiences. Practice and policy implications are discussed, including how the provision of tailored clinical and peer supports can assist gay men in the bereavement of a same-sex partner to suicide. The findings detailed in this study highlight the need for interventions to de-stigmatise mental illness and suicide within and outside the gay community.